New Records of Non-Diatom Algae in Aquatic Habitat along Greater Zab River Path from Bekhma to Gwer District in Erbil Province, Iraq (Baghdad Science Journal, 2023)
A study of non-diatom algal species composition in twelve sites from Greater Zab River path within Erbil Province, was carried out from April 2021 to January 2022 with monthly sample collection in twelve studied sites. Among them site 4,5,6,7 and 9 are the first for algal study in this area. The 112 different species of algae belong to 33 genera, 25 families, 13 orders and 4 divisions have been identified. The predominant genera included Spirogyra and Cosmarium 17, 8 taxa respectively. 13 taxa were new recorded to Iraqi Kurdistan algal flora and 9 of them were new recorded to Iraqi algal flora: Botryosphaerella sudetica, Muriella magna, Gloeotaenium loitlesbergianum, Apiocystis brauniana, Anabaena oscillarioides, C. distentum, C. tutum, C. contractum var. minutum, kirchneriella irregularis, Oedogonium suecicum f. australe, Coelastrum indicum, Oocystis lacustris, and Pediastrum braunii. Also, there were three new genera for Iraqi algal flora which including: Botryosphaerella, Muriella and Apiocystis. A brief description as well as the measurement is given for each species. Water temperatures ranged from 17.3 to 20.08 ºC, hydrogen ion concentration and electrical conductivity value ranged from 7.44 to 7.88 and 433.20 to 721.56 μS.cm-1 for all studied sites respectively. The aim of this study is to identify algal taxa in studied sites.